Early full enteral feeding in very low birth weight babies on day one - Bhosgi, Revanasiddappa; Harwalkar, Kirankumar (International Journal of Contemporary Pediatrics, 2021)
Background: Nutrition in very low birth weight babies is most important factor in early improvement of neonate. It also decides duration of stay in intensive care unit. Objectives of the current study were to initiate required full enteral feed at the earliest and to know the outcome of such neonates. Methods: It is a hospital based retrospective study conducted from October 2019 to December 2019 in Gulbarga institute of medical sciences, Kalaburagi. 40 clinically stable VLBW neonates on day 1 started on enteral feeding are included in the study. Babies with birth weight more than 1.5 kgs or less than 1 kg, hemodynamically unstable at start of feeds are excluded from the study. Collected data is analysed by SPSS 17. Results: Total 40 VLBW babies were included in the study. Among them, 28 neonates tolerated feeds, were improved & discharged early with an average duration of stay of 16days with early birth weight gain by 14 days. 10 neonates had feed intolerance with signs of Necrotizing enterocolitis during course of treatment, were improved and discharged with an average duration of stay of 22 days. Mortality was seen in 2 neonates due to associated sepsis. Conclusions: Initiation of full enteral feeds in stable VLBW babies is effective mode for improvement, weight gain and early discharge from hospital.